Environmental tobacco smoke and children's health - Sang-Hyun Hwang; Jong Hee Hwang; Jin Soo Moon; Do-Hoon Lee (Korean Journal of Pediatrics, 2012)
Passive exposure to tobacco smoke significantly contributes to morbidity and mortality in children. Children, in particular, seem to be the most susceptible population to the harmful effects of environmental tobacco smoke (ETS). Paternal smoking inside the home leads to significant maternal and fetal exposure to ETS and may subsequently affect fetal health. ETS has been associated with adverse effects on pediatric health, including preterm birth, intrauterine growth retardation, perinatal mortality, respiratory illness, neurobehavioral problems, and decreased performance in school. A valid estimation of the risks associated with tobacco exposure depends on accurate measurement. Nicotine and its major metabolite, cotinine, are commonly used as smoking biomarkers, and their levels can be determined in various biological specimens such as blood, saliva, and urine. Recently, hair analysis was found to be a convenient, noninvasive technique for detecting the presence of nicotine exposure. Because nicotine/cotinine accumulates in hair during hair growth, it is a unique measure of long-term, cumulative exposure to tobacco smoke. Although smoking ban policies result in considerable reductions in ETS exposure, children are still exposed significantly to tobacco smoke not only in their homes but also in schools, restaurants, child-care settings, cars, buses, and other public places. Therefore, more effective strategies and public policies to protect preschool children from ETS should be consolidated.